2016
DOI: 10.1016/j.jval.2016.03.273
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty Post Acute Care Costs By Discharge Status

Abstract: Outpatient costs represented 82% of total costs (antineoplastics 26%, supportive care 15%, office visits 4%, labs/diagnostics 1%, radiation/surgery 1%, other drugs 19%, procedures 15%). Inpatient costs (emergency department [ED] visits/hospitalizations) represented 18% of total cost for patients with inpatient claims; mean total cost (N= 3552, 67%) was $119,034. ConClusions: The study shows high TCC for advanced NSCLC; with increasing costs in later LOTs. Nearly 70% of patients had ED visits/hospitalizations; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This was illustrated by Zeng and Waldo in a retrospective review entailing 8,801 TKA surgeries. 44 In their study, the authors reported significant increases in 90-day costs for inpatient rehabilitation (þUS $22,921; p < 0.05), skilled nursing facility (þUS$15,489; p < 0.05), and home health care (þUS$6,620; p < 0.05). Similarly, in a retrospective review of 2,328 consecutive TKA recipients, Barad et al 45 revealed that a decrease in mean LOS (2 days to 1.3 days) coupled with an increased discharge to home (9% to 53%) translated to a mean costs savings of US $3,245.…”
Section: Discussionmentioning
confidence: 94%
“…This was illustrated by Zeng and Waldo in a retrospective review entailing 8,801 TKA surgeries. 44 In their study, the authors reported significant increases in 90-day costs for inpatient rehabilitation (þUS $22,921; p < 0.05), skilled nursing facility (þUS$15,489; p < 0.05), and home health care (þUS$6,620; p < 0.05). Similarly, in a retrospective review of 2,328 consecutive TKA recipients, Barad et al 45 revealed that a decrease in mean LOS (2 days to 1.3 days) coupled with an increased discharge to home (9% to 53%) translated to a mean costs savings of US $3,245.…”
Section: Discussionmentioning
confidence: 94%
“…Preoperative workup d $260 [29][30][31] $260 [29][30][31] $272 [29][30][31] $544 [29][30][31] Anesthesia costs $292 33,38 $292 33,38 $418 33,38 $682 33,38 Surgery/procedure costs $10,785 30,32 $10,785 30,32 $14,024 30,32 $24,809 30,32 Surgeon/proceduralist fee $1,409 30,31 $1,409 30,31 $1,592 30,31 $2,659 30,31 Postoperative care e $101 29,30,35 $101 29,30,35 $101 29,30,35 $4,128 29,30,35 Postacute rehab/physical therapy $6,397 29,34,36,37 $6,397 29,34,36,37 $6,397 29,34,36,37 $16,386 29,34,36,37 Preoperative CT scan -$368 29,30 --…”
Section: Transition Probabilitiesmentioning
confidence: 99%
“…We used Medicare reimbursement schedules to estimate the costs of preoperative office visits, laboratory tests, imaging, inpatient hospital costs, surgeon and anesthesia fees, postoperative care, and rehabilitation [29][30][31][32][33][34][35][36][37][38] (Table 1).…”
Section: Costsmentioning
confidence: 99%
“…The true cost of these procedures in this patient population includes their post-hospital expenses. A total of 42.8% of the octogenarians and nonagenarian patients needed to be discharged to an SNF, which has been shown to add 15,000 USD in post-acute care costs [27]. Additional healthcare expenditures to care for discharge disposition, readmissions, or complications are not captured in the current study and should be the focus of future research.…”
Section: Discussionmentioning
confidence: 91%